Alternativas para garantizar la seguridad económica en la vejez : desafíos para Colombia (2016)
ABSTRACT: Aging in Colombia in a context of high poverty, income inequality and social inequity in confrontation with consumer behavior and the need for services to ensure quality of life, they force us to think in economic security in old age. In this vein, and in the mood to think about aging and old age from all perspectives of development, three strategies that enable value creation arise for older people remain active in society, income guarantee alternatives allowing them economic security and quality of life to the structural barriers imposed by the General Pension System.